STRATEGIES FOR STRENGTHENING THE PERFORMANCE OF GOVERNMENT AGENCIES TO COMBAT HUMAN TRAFFICKING IN THE SPECIAL BORDER ECONOMIC ZONE, CHIANG RAI PROVINCE - Treeaekanukul, Silas (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2020)
The purpose of this research was to study the working conditions, assess the operational efficiency and propose strategies to strengthen the performance of government agencies to combat human trafficking in special border economic zones, Chiang Rai Province. Mixed method were used, For Qualitative research collected data by doing workshops from the population totally 38 agencies, which are both the public and private sectors that are responsible for their operations to combat human trafficking in the special border economic zone in the areas of Mae Sai District, Chiang Saen District and Chiang Khong District, Chiang Rai Province. For quantitative research, data were collected by questionnaires from a sample that designs by setting of quota 5 persons from 38 agencies totally 190 persons. The research results found that, the strengths of the operating conditions of the department to combat human trafficking are: working closely with people and the strength in performing. The weaknesses are not enough budgets, personnel administration is still not conducive to work, lack of a continuous and systematic in human resource development plan and some operators do not cooperate in problem resolution. Overall for work efficiency was at a medium level, strengthening strategy, evaluation of suitability is at high to highest level. The vision which mention is " Professional skill driving operations to combat human trafficking in Chiang Rai special border economic zone.”